Analisis kesehatan mental di masyarakat - Fitriani, Larissa Nadira; Purba, Vinsensia; Hasanah, Yunita Nur; Rozak, Rama Wijaya Abdul (ARKA INSTITUTE, 2023)
Not everyone can understand mental health. Mental health is a person's psychological and emotional condition that greatly affects one's behavior, thoughts and actions. Therefore, mental disorders can cause anxiety due to pressure from various aspects. This research was conducted using a quantitative method in the form of a survey by filling out a questionnaire as the main instrument for data collection. Where the questionnaire will be used to analyze mental health in Indonesian society. Techniques with questionnaire analysis are also used to see how literate Indonesian people are about mental health. The population in this study were students from several universities in Indonesia. While the sample was 122 students who were taken randomly. So it can be concluded that the purpose of this study is to analyze how mental health in Indonesian society.